2007
DOI: 10.1002/jcp.21114
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Rho/ROCK and MLCK in TNF‐α‐induced changes in endothelial morphology and permeability

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is known to induce changes in endothelial cell morphology and permeability, but the mechanisms have not been extensively characterized. TNF-alpha rapidly induced RhoA activation and myosin light chain phosphorylation, but caused only small changes to cortical F-actin, without significantly increasing paracellular permeability up to 30 min after stimulation. TNF-alpha subsequently caused a progressive increase in permeability and in stress fiber reorganization, cell elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
214
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(243 citation statements)
references
References 41 publications
24
214
5
Order By: Relevance
“…It was reported that the low TEER was associated with irregular cell shape, when studied morphologically (Tretiach et al, 2003), and alterations in the permeability of the vascular endothelium (Bucana et al, 1988). McKenzie & Ridley (2007) found that TNF-a subsequently caused a progressive increase in permeability and in stress fibre reorganization, cell elongation and intercellular gap formation over 8-24 h. Consistent with the increased permeability, occludin and JAM-A were removed from tight junctions and ZO-1 was partially redistributed (McKenzie & Ridley, 2007). Similar results were obtained in the present study.…”
Section: Permeability Of Dengue Virus-infected Endothelial Cellssupporting
confidence: 90%
“…It was reported that the low TEER was associated with irregular cell shape, when studied morphologically (Tretiach et al, 2003), and alterations in the permeability of the vascular endothelium (Bucana et al, 1988). McKenzie & Ridley (2007) found that TNF-a subsequently caused a progressive increase in permeability and in stress fibre reorganization, cell elongation and intercellular gap formation over 8-24 h. Consistent with the increased permeability, occludin and JAM-A were removed from tight junctions and ZO-1 was partially redistributed (McKenzie & Ridley, 2007). Similar results were obtained in the present study.…”
Section: Permeability Of Dengue Virus-infected Endothelial Cellssupporting
confidence: 90%
“…Previous studies have shown that MLCK plays a central role in the regulation of intestinal epithelial TJ barrier function (41,49,55,56). MLCK activation has been shown to be a central mechanism that regulates both pharmacologic (39 -41) and physiologic (42) induced opening of intestinal TJ barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in primary cultures of retinal endothelial cells, TNF-a induces changes in protein levels of ZO-1 and claudin-5 as early as 6 h after treatment (59), and long-term exposure to TNF-a correlates with redistribution of junctional adhesion molecule, occludin, and ZO-1 proteins from the cell-cell junction (30). In addition, treatment of peripheral microvascular endothelium with TNF-a and IFN-g results in focal loss of VE-cadherin-mediated intercellular adhesion in areas of endothelial barrier breakdown (12).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a and IFN-g modulate paracellular permeability and transendothelial electrical resistance of hCMEC/D3 cells Previous studies have shown that treatment of human peripheral microvascular endothelial cells with either TNF-a alone or in combination with IFN-g induces an increase in paracellular permeability (28)(29)(30). To evaluate the capacity of proinflammatory cytokines to disrupt the gate properties in hCMEC/D3 cells, we performed paracellular permeability studies using the hydrophilic tracer 70 kDa FITC-dextran.…”
Section: Expression Of Tnf-a and Ifn-g Receptors By Hcmec/d3 Cellsmentioning
confidence: 99%